Profile of Chronic Tonsillitis Patients Undergoing Tonsillectomy - Mohammad Dwijo Murdiyo; Bio Swadi Ghutama (Journal of Medical Practice and Research, 2026)
Tonsillitis is an inflammation of the palatine tonsils, an important part of Waldeyer's ring that plays a role in defending the mucous membranes of the respiratory and digestive tracts. Chronic tonsillitis is prolonged inflammation of the tonsils, usually after several episodes of recurrent acute tonsillitis, at least seven times a year. Treatment can be conservative (medical) or surgical, such as tonsillectomy. This study aims to determine the characteristics of patients with chronic tonsillitis who underwent tonsillectomy at Saiful Anwar General Hospital during the period of 2022-2024. This study aims to describe the demographic characteristics, clinical presentations, surgical indications, procedures and postoperative outcome of patients with chronic tonsillitis who underwent tonsillectomy at Saiful Anwar General Hospital during the period of 2022-2024. This study is a retrospective descriptive observational study with data collected from medical records of patients diagnosed with chronic tonsillitis who underwent surgery. A total of 135 patients were recorded. The most common age group was around 5–11 years (42.2%). There were more male patients than female, with 84 men (62.2%) and a ratio of 1,6:1. The most common chief complaint was throat pain (53.3%). The most frequently observed tonsil size was T3 (43.7%), and (45.2%) of patients also had adenoid hypertrophy. The most common indication for surgery was infection (49.6%), with the most frequently performed procedure being adenotonsillectomy (73.3%). The most commonly used surgical technique was cold dissection (65.2%). Postoperative bleeding complications occurred in 3 patients (2.2%). The most common length of hospital stay was 2 days (38.5%). Most patients with chronic tonsillitis who underwent surgery were children aged around 5–11 years, predominantly male, with T3 tonsil sized and associated adenoid hypertrophy. The most common indication for surgery was infection, with adenotonsillectomy using the cold dissection technique as the primary method, demonstrating minimal complications and a short hospital stay.